Effect of PCSK9 inhibitor on early neurological deterioration in acute ischemic stroke patients with a history of coronary heart disease: a study protocol for a randomized controlled trial in Dalian, China - Xing Gong; Xinting Yu; Lanlan Pu; Yang Jiao; Lin Liu; Hua Cao; Xiaofei Ji (Trials)
Abstract Background Early neurological deterioration (END) is a critical determinant influencing the short-term prognosis of acute ischemic stroke (AIS) patients and is associated with increased mortality rates among hospitalized individuals. AIS frequently coexists with coronary heart disease (CHD), complicating treatment and leading to more severe symptoms and worse outcomes. Shared risk factors between CHD and AIS, especially elevated low-density lipoprotein cholesterol (LDL-C), contribute to atherosclerosis and inflammation, which worsen brain tissue damage. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors offer a promising treatment option. They effectively lower LDL-C levels and may help reduce END in AIS patients with CHD. This study aims to evaluate how effective PCSK9 inhibitors are in reducing END among this high-risk group and to provide new insights for treatment strategies. Methods This is a prospective, randomized, parallel-group, blinded-endpoint, single-center clinical study. A total of 156 AIS patients with a history of CHD and within 24 h from symptom onset will be recruited and randomized in a 1:1 allocation to either the PCSK9 inhibitor combined with statin treatment group (PI group) or the statin monotherapy group (AT group). The PI group will receive a combination therapy consisting of evolocumab and rosuvastatin calcium tablets, while the AT group will receive only oral rosuvastatin calcium tablets. The trial duration will last for 90 days and comprise three phases: screening, treatment intervention, and follow-up assessments. Participants will undergo comprehensive examinations and assessments on days 1, 7, 30, and 90 after enrollment. Discussion This study aims to investigate the potential preventive effects of PCSK9 inhibitors on END in AIS patients with a history of CHD. A positive outcome from this trial could provide novel clinical strategies for reducing the incidence of END and improving the short-term prognosis among these stroke patients. Trial registration China Clinical Trial Registry, ChiCTR2300078198. Registered on 30 November 2023.